Idelalisib for optimized CD19‐specific chimeric antigen receptor T cells in chronic lymphocytic leukemia patients. Issue 5 (28th February 2019) - Stock, Sophia; Übelhart, Rudolf; Schubert, Maria‐Luisa; Fan, Fuli; He, Bailin; Hoffmann, Jean‐Marc; Wang, Lei; Wang, Sanmei; Gong, Wenjie; Neuber, Brigitte; Hückelhoven‐Krauss, Angela; Gern, Ulrike; et al.
Abstract : Despite encouraging results with chimeric antigen receptor T (CART) cells, outcome can still be improved by optimization of the CART cell generation process. The proportion of less‐differentiated T cells within the transfused product is linked to enhanced in vivo CART cell expansion and long‐term persistence. The clinically approved PI3Kδ inhibitor idelalisib is well established in the treatment of B cell malignancies. Besides B cell receptor pathway inhibition, idelalisib can modulate T cell differentiation and function. Here, detailed longitudinal analysis of idelalisib‐induced effects on T cell phenotype and function was performed during CART cell production. A third generation CD19.CAR.CD28.CD137zeta CAR vector system was used. CART cells were generated from peripheral blood mononuclear cells of healthy donors (HDs) and chronic lymphocytic leukemia (CLL) patients. Idelalisib‐based CART cell generation resulted in an enrichment of less‐differentiated naïve‐like T cells (CD45RA+CCR7+), decreased expression of the exhaustion markers PD‐1 and Tim‐3, as well as upregulation of the lymph node homing marker CD62L. Idelalisib increased transduction efficiency, but did not impair viability and cell expansion. Strikingly, CD4:CD8 ratios that were altered in CART cells from CLL patients were approximated to ratios in HDs by idelalisib. Furthermore, in vivo efficacy of idelalisib‐treated CART cells was validated in a xenograft mouse model. Intracellular TNF‐α and IFN‐γ production decreased in presence of idelalisib. This effect was reversible after resting CART cells without idelalisib. In summary, PI3Kδ inhibition with idelalisib can improve CART cell products, particularly when derived from CLL patients. Further studies with idelalisib‐based CART cell generation protocols are warranted. Abstract : What's new? Despite encouraging results with anti‐CD19 chimeric antigen receptor T (CART) cell therapy for B cell malignancies, clinical outcome could still be improved by optimization of the CART cell generation process. Here, the authors show that ex vivo PI3Kδ inhibition by the B cell malignancy drug idelalisib during CART cell generation can increase the proportion of less‐differentiated T cells and lead to a less exhausted T cell phenotype. Idelalisib optimized the phenotype of CART cells derived from chronic lymphocytic leukemia (CLL) patients. This study thus provides important novel and potentially practice‐changing findings for CART cell generation and expansion, especially for CLL patients.